Trustees and educational centres of Ukrainian religious communities of Galicia as a form of compensation for family education (end of XIX – the first half of XX century) - Myshchyshyn, Iryna (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2014)
At the end of the nineteenth century – beginning of the twentieth. century thanks to complex social and historical conditions, given the lack of family education on the initiative of prominent representatives of religious congregations and the Ukrainian Greek Catholic Church a system of pre-school education was developed. Due to the great work of the sisters, sister-teachers developed an original system of the harmonious raising and developing of children. Devoting themselves to the education of Ukrainian children, nuns demonstrated the effectiveness of public education and demonstrated the need for its development where there was a lack of the influence of the family and a limited educational environment.
Keywords: nuns; Catholic Church; children's ward; nursery school; upbringing; Galicia